Postcard from August Friedrich Horstmann to Georg Bredig, November 1927 - Horstmann, August Friedrich (1927)
Thank you note from August Friedrich Horstmann (1842-1929) to Georg Bredig (1868-1944).
Keywords: Horstmann, August Friedrich, 1842-1929; Bredig, Georg, 1868-1944; Thank-you notes; Chemists